2010
DOI: 10.1111/j.1442-2018.2010.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Turkish version of the Depression Coping Self‐efficacy Scale

Abstract: Reliable and valid instruments are needed to assess and deal with the problems that are encountered by depressed patients in psychiatric nursing practice. The aim of this study was to assess the reliability and validity of the Turkish version of the Depression Coping Self-efficacy Scale. A descriptive and correlation design was used to determine the psychometric properties of the Scale. The study population was 105 depressed inpatients from acute psychiatry services. The study confirmed that the Scale is relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…If the result is below 50%, the individual's self-efficacy is regarded as low, a moderate result is between 50 and 75%, and a high result is over 75% (Perraud 2000). Albal et al (2010) did the Turkish adaptation of the scale, and they found a reliability coefficient of 0.94 (Albal et al 2010). The Cronbach's alpha reliability coefficient of the scale in this study was calculated to be 0.72.…”
Section: Dcsesmentioning
confidence: 58%
See 4 more Smart Citations
“…If the result is below 50%, the individual's self-efficacy is regarded as low, a moderate result is between 50 and 75%, and a high result is over 75% (Perraud 2000). Albal et al (2010) did the Turkish adaptation of the scale, and they found a reliability coefficient of 0.94 (Albal et al 2010). The Cronbach's alpha reliability coefficient of the scale in this study was calculated to be 0.72.…”
Section: Dcsesmentioning
confidence: 58%
“…Albal et al. () did the Turkish adaptation of the scale, and they found a reliability coefficient of 0.94 (Albal et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations